Organizational Commitment and Organizational Citizenship Behavior as Predictors of Employee Performance - Kantirahayu, Dina Subekti; Sumunar, Tika; Yuniawan, Ahyar (Economic and Business Horizon, 2025)
Understanding the factors that enhance employee performance has become increasingly important amid continuous organizational transformation. This study investigates the role of organizational commitment and Organizational Citizenship Behavior (OCB) in shaping employee performance at a leading power company in Indonesia that is experiencing rapid digital and structural changes. Using a quantitative research design, data were collected through a structured questionnaire involving 150 respondents and analyzed using inferential statistical methods. This study employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) as the data analysis technique, utilizing a second-order construct model to capture higher-order latent variables. The results showed that all variables-organizational commitment and OCB-contributed positively and significantly to improved employee performance. Employees who are emotionally committed to the organization, can effectively balance professional and personal responsibilities, and voluntarily engage in organizational citizenship behaviors tend to exceed performance expectations. These findings not only enrich the theoretical discourse in human resource management but also provide practical strategies for organizations seeking to build a resilient and high-performing workforce in an increasingly complex environment.